2020
DOI: 10.1088/1757-899x/872/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Study of technologies implemented in the operation of SF6 switches

Abstract: This research aims to evaluate the trends in the publication of papers on issues related to power circuit breakers, aimed at the technologies implemented, as well as those countries with higher level of publications, making a comparison between authors, research institutes, and a description of the last 10 years with more publications. All the information found in this report is compiled in bibliographic databases such as books of substation designs and research papers with a focus on electrical protection equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The aging or degradation of the oil used as insulation and cooling medium in transformers is mainly due to changes in the molecular structure of the dielectric. These changes are related to the decomposition of the insulation properties of power cables [40]- [42]. In this context, current diagnostic methods must develop intelligent techniques in the incipient detection of degradation of insulating materials in power transformers.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The aging or degradation of the oil used as insulation and cooling medium in transformers is mainly due to changes in the molecular structure of the dielectric. These changes are related to the decomposition of the insulation properties of power cables [40]- [42]. In this context, current diagnostic methods must develop intelligent techniques in the incipient detection of degradation of insulating materials in power transformers.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…A study of the RSM and the Angle method [27], [28] to design protection systems against the direct incidence of atmospheric discharges on structures. This study shows, through mathematical modeling, that both methods are closely linked and that they can be used safely in the dimensioning of protection systems since they comply with the technical requirements demanded by the standards [29]- [33].…”
Section: Methodsmentioning
confidence: 99%
“…The ODP for G 3 gas is equal to zero but for SF6 gas equal to 0.08 which means that using the proposed gas could lead to more enhancement for ODP [12]. From 1994 to 2016 as shown in Figure 2 the concentration of SF6 gas in the atmosphere where shown that during the last five years the concentration of SF6 gas was increased by 20% [13], [14]. So, the potential alternative gas should be worked in all industrial works to reduce the main effect of this gas (greenhouse effect) which is one of the important recommendations of the Kyoto protocol that needed to be achieved [15].…”
Section: Introductionmentioning
confidence: 94%